Regulation of Clinical Trials under the European Union Law (Summary) - A. H. Abashidze; V. S. Malichenko (Московский журнал международного права, 2013)
The European Union is a market leader in clinical research, and this status requires uniform legislation in this area. However, all attempts to unify legislation had the opposite effect, leading to a reduction of investment in R & D area. To remedy the situation, the EU adopted Regulation, which aims to promote investments in R & D area.